Decomposição de Staurastrum iversenii Neygaard var. americanum: efeitos da qualidade do recurso, da disponibilidade de oxigênio e da temperatura - Pacobahyba, Lucilia Dias (Universidade Federal de São Carlos, 2002)
In this work the decomposition aspects of the Staurastrum iversenii Nygaard var. americanum phytoplankton species, isolated from the Barra Bonita Reservoir (22 degrees 29 minutes S e 48 degrees 34 minutes W), were approached; as resource of the decomposition were used: cells (ruptured and whole) and polysaccharide of higher and lower molecular masses. Were approached, still, the effects of the following variables: temperature and concentration of dissolved oxygen. Therefore, decomposition chambers were set up in laboratory with cells (ruptured and whole) and polysaccharides of higher and lower molecular masses deriving from S. iversenii. Based on the quantifications of the organic carbon concentrations, the decomposition processes of the resources were described and the kinetic coefficients evaluated. These descriptions constituted the base of the models proposed for the resource decomposition. These models allowed to infer that the used substrata constituted from a structural point of view, of composed heterogeneous, presenting labile and refracting fractions. In relation to the consumption of oxygen, the decomposition of the ruptured cells was observed to be faster than that of the whole cells; for the polysaccharides, the consumptions of oxygen were faster in the mineralization of the fractions of high molecular mass. The temperature influenced the speeds of the processes involved with the mineralization of the refracting fractions, besides altering the mineralization routes of the resources; it, also, induced the occurrence of alterations of the stoichiometric (O/C) relationships of the processes. It was possible to verify that the sugars which form these polysaccharides contributed with the supply of energy to the microorganisms during a long period. The proposed mathematical models were shown to be sensitive to the experimental results. The degradation of S. iversenii can contribute to the maintenance of the processes connected to the maintenance of the Barra Bonita Reservoir microbial loop.
Keywords: Fictoplâncton; Mineralização aerobia; Temperatura; Polissacarídeos excretados; Modelos cinéticos; Consumo de oxigênio; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS